Striving for Superiority Between U.S. And China: The Rivalry Leading to the Trade War (1978-2020) - KAYHAN, OSMAN SELMAN (İstanbul Kültür Üniversitesi, 2021)
The relations between the United States and China is going through a difficult period in terms of International Political Economy. The adversity leads the world into apprehension regarding the peace and stability in the world order. The rapid growth of China following the 1978 economic reform and modernization process was a critical determinant for their future policies. Despite the obstacles which decelerate the sudden growth of China, the impact of the country to the world politics was still outrageous. Therefore, the favorable amity between the United States and China in the aftermath of the economic reforms turned into agnosticism. As the real political intention of the rising China was mysterious to the United States officials, the process of transition in the relations was critical. The changing power dynamics after the end of the Cold War had a significant impact on the policies of the countries. The unexpectedly successful rise of China brought about many questions in relation to their intention whether they will follow policies in line with the status quo or their own national interests. The China perception in the United States evolved into a negative perspective following the tragic event in the Tiananmen Square where the demonstrations were surpassed in a violent way. The China threat perception gained a significant popularity across the country and was mentioned in scholarly articles. Even though the China threat perceptions appeared to be only as discourses, the fact that it was supported by the public and scholars was critical in order to have impact and pressure on the policymaking mechanism of the United States. However, the United States was not in favor of taking a negative stance against China considering their increased impact in the world politics. In this line, the government of the United States followed a strategic partnership policy. However, the ongoing rise of China increased the criticism against the engagement policies of the United States. The fact that China threat discourses were supported by the theoretical frameworks and increased military expenditures proved that the discourses may turn into reality. This process brought about questions regarding rise of China and the possible threat to an existing world order. The reaction of the United States, in this case, is critical whether they shape the policies towards China in line with the threat perceptions or continue to follow moderate policies.
Amerika ve Çin Arasındaki Üstünlük Arayışı: Ticaret Savaşına Götüren Rekabet (1978-2020)
▪ Yüksek lisans tezi.